2006
DOI: 10.1192/apt.12.3.214
|View full text |Cite
|
Sign up to set email alerts
|

The neuropsychiatry of multiple sclerosis

Abstract: Kate Jefferies is a specialist registrar in old age psychiatry at Farnham Road Hospital (Farnham Road, Guildford GU2 7LX, UK. Email: katejefferies@tiscali.co.uk). She is training in old age and general adult psychiatry and her special interest is neuropsychiatry.Abstract Multiple sclerosis is the most common disabling neurological illness affecting young and middle-aged adults. Although attention has tended to focus mainly on its neurological manifestations, reports of the presence of neuropsychiatric symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 38 publications
1
24
0
1
Order By: Relevance
“…Those symptoms which may more accurately indicate a comorbid depressive episode include a pervasive low mood, anhedonia, diurnal mood variation, suicidal ideation, pessimistic or negative patterns of thinking and impaired functionality unrelated to or out of proportion to one’s physical disability (table 1). 9 …”
Section: Major Depressive Disordermentioning
confidence: 99%
See 2 more Smart Citations
“…Those symptoms which may more accurately indicate a comorbid depressive episode include a pervasive low mood, anhedonia, diurnal mood variation, suicidal ideation, pessimistic or negative patterns of thinking and impaired functionality unrelated to or out of proportion to one’s physical disability (table 1). 9 …”
Section: Major Depressive Disordermentioning
confidence: 99%
“…This increased rate is not solely attributable to the effects of steroid treatment although up to one-third of individuals experience a corticosteroid-induced manic episode or to antidepressant-induced (hypo)manic states 74 75. Other agents have also been implicated in causing episodes of (hypo)mania including baclofen, dantrolene, tizanidine and psychoactive substances 9. Drug-induced manic symptoms appear generally to be dose dependent, occur early in treatment and are usually responsive to treatment 76.…”
Section: Bipolar Affective Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…Depression is common, with raised suicide risk. Psychosis is uncommon in MS and is distinct from schizophrenia as it has a later age at onset, quicker resolution, fewer relapses, better response to treatment and a better prognosis (Jefferies 2006). Schizophreniform psychosis may be secondary to steroid treatment.…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…In his original description of MS, Jean Martin Charcot, the father of modern neurology (2), noted loss of memory and reduced understanding (1). In 1877, Charcot observed that people with MS might show "marked enfeeblement of the memory, conceptions are formed slowly, and intellectual and emotional faculties are blunted in their totality" (3).…”
Section: Introductionmentioning
confidence: 99%